An Analysis of Decision-Making Arbitration and Settlement on Employee-Transfer Court Cases - Govindasamy, Munusamy (2024)
The commercial enterprises have grown with branches in districts and states, national, regionally and internationally to accommodate ever-growing demands for quality products, services and consultancies, with affordable or reasonable costs. Deployment of capital and labour is the main key to supporting production operations and sustaining logistics-supply chain for all industries; one without the other cannot survive, develop and grow organization business profitability specifically and country economic wealth and people welfare in general. Invariably, Associations representing the employers and Trade Unions representing the workers are confronted with labour- relations issues that propel each of them to protect the welfare or negotiate the disputed interests of their respective members. In this context, as the dispute-negotiation process is disrupted or has reached a stalemate, for one reason or another, the so-called Industrial Disputes and the aggrieved parties can continue to seek redress beyond the decision-arbitration intervention of the Industrial Relations Department of the Industrial Court, into the ambit of review-settlement decisions by the High Court, Appeal Court and Federal Court in pursuit of a justifiable claim for judgmental decision on reasonable compensation. In this thesis, Industrial Disputes arising from disputed employee-transfer cases are analysed, employing the legal bases for mainly Malaysian cases and the Commonwealth cases as references for judgmental decision-making, arbitration and settlement for contractual disputes involving diverse issues surrounding employee-transfer involving bona fide and mala fide transfers representing a widespread of grievances, grouses or complaints from mostly aggrieved and disrupted workmen. The 14 selected cases, based on a set of 7 pair-cause similar premise-issue such as transfer demotion, insubordination, change of ownership, change of job functions, departmental transfer, different legal entity, and no transfer clause in Appointment Letter are analysed and resolved legally. The expected output of this case-study based on the ex post facto method of review-analysis, in the form of judgement-resolution decisions, provide the retrospective insight into and critique of how, and to what extent, the impact of the decisions-outcome has affected the employer (organizations), employee (workmen and Associations), legal arbitrators (courts) in terms of labour relations and its statutory provisions (the Acts), policy governance (Ministry of Human Resource) and overall productivity of national economic wealth and citizenry welfare. The conclusion provides a directional indicator of future redress-award solutions beyond the applications of conventional arbitration and settlement models into the advocacy of water-tight contract-specific terms and conditions of employment into the digital era of industrial ventures and commercial enterprises, during and post-COVID19 pandemic era. The fourteen cases selected produce the final desired employer-employee output-outcome of the wisdom of judicial judgmental decisions.